Learning Methods Based on Work Practices or Internship can be Implemented in Entrepreneurship Campus - Nangoy, Abraham Daud; Kartikasari, Cynthia Yohanna (Syntax Literate, 2024)
Kampus Merdeka is a work practice or internship program organized by the Minister of Education and Culture (Kemendikbud) in early 2020, aiming to be a media that can improve student skills. This article discusses how work practice or internship-based learning methods can be used on business education-based campuses. This research uses phenomenological and autoethnography methods by analyzing students' experiences during their internships. This research shows that : (1) The internship program motivates students to become entrepreneurs. (2) The internship program develops students' communication skills through direct interaction with the workforce. (3) The internship program builds students' confidence to collaborate with company partners. (4) The internship program encourages students to be creative in their work. (5) The internship program helps them determine the field of work they want to pursue after graduating. (6) The internship program is an option that has a positive impact.